Islamic Public Relations in Issue Management and Media Relations - Muhammad Hatta; Marhamah Marhamah; Hazan Sazali (SAINTIS Publishing, 2025)
This article examines the Islamic Public Relations (PR) approach in issue management and media relations in Islamic institutions in Indonesia. The Islamic approach in public relations emphasizes the values of honesty, openness, responsibility, and manners in communication. In the context of a society that is experiencing information polarization and increasing distrust of religious institutions and the media, the role of Islamic PR is important to build credibility and maintain the image of the institution. Through a qualitative-descriptive approach based on literature studies and case studies on several Islamic organizations and Islamic boarding schools, this article explains how Islamic values are applied in issue management and establishing healthy and strategic relationships with the mass media. The results of the analysis show that the Islamic PR approach is able to build a calming, honest, and solutive narrative in the midst of a crisis of public issues. It is necessary to strengthen media literacy and Islamic PR training based on maqāṣid al-syarī'ah so that Islamic institutions are able to appear as communication actors who are trusted by the public.